A security analysis of authentication and authorization implemented in web applications based on the REST architecture - Tomasz Muszyński; Grzegorz Koziel (Journal of Computer Sciences Institute, 2020)
The purpose of this article is to prepare a security analysis of authentication and authorization mechanisms in web applications based on the REST architecture. The article analyzes the problems encountered during the implementation of the JSON Web Token (JWT) mechanism. The article presents examples of problems related to the implementation of authorization and authentication, and presents good practices that help ensure application security.